Fast detection of extrasynaptic GABA with a whole-cell sniffer - Christensen, Rasmus K.; Petersen, Anders V.; Schmitt, Nicole; Perrier, Jean-François (Frontiers in Cellular Neuroscience, 2014)
Gamma-amino-butyric acid (GABA) is the main inhibitory transmitter of the brain. It operates by binding to specific receptors located both inside and outside synapses. The extrasynaptic receptors are activated by spillover from GABAergic synapses and by ambient GABA in the extracellular space. Ambient GABA is essential for adjusting the excitability of neurons. However, due to the lack of suitable methods, little is known about its dynamics. Here we describe a new technique that allows detection of GABA transients and measurement of the steady state GABA concentration with high spatial and temporal resolution. We used a Human Embryonic Kidney (HEK) cell line that stably expresses GABAA receptors composed of α1, β2, and γ2 subunits. We recorded from such a HEK cell with the whole-cell patch-clamp technique. The presence of GABA near the HEK cell generated a measurable electric current whose magnitude increased with concentration. A fraction of the current did not inactivate during prolonged exposition to GABA. This technique, which we refer to as a “sniffer” allows the measurement of ambient GABA concentration inside nervous tissue with a resolution of few tens of nanomolars. In addition, the sniffer detects variations in the extrasynaptic GABA concentration with millisecond time resolution. Pilot experiments demonstrate that the sniffer is able to report spillover of GABA induced by synaptic activation in real time. This is the first report on a GABA sensor that combines the ability to detect fast transients and to measure steady concentrations.